Probe survival course [videorecording] - Lazaro, Cheche; Ramos, Angie (Quezon City Probe Productions, 1993)
Recalls staffer's experiences in production and field assignments. Tackles also the trip to Subic Naval Base and jungle training.
VHS.
Keywords: Probe Team (Television program)